Study and Analysis of the Characteristics of the Iraqi Style in Shams Rumi's Ghazal Divan - سعید, عمر محمد (Sulaimani Journal for Humanities, 2019)
Mawlana Jalaladin Muhammad Balkhy is one of the biggest Iranian poets. He lives at the 7th century. He is treated as the highest poet among the poets era in the midlle east. According to his poetic style, he is guessed as one of the leader of the Iraqi style; in spite of this, he has his special Iraqi style also. The content of his poems are about: Love (Eishq) and gratitude (Erfan). The Gratitude poem is reached to the highest point by him. Because of our research is about Mawlana’s poem style and Iraqi style poem that’s why the definision of style and its types are need. Style is the special type of poem’s writing and it is how the poet says his ideas, his senses. The Persian poetic style divided into four kinds; they are: Khorasany style, Iraqi style, Indian style and returning poetic style. In this thesis shed lite on the biography’ poetic style, ideas and imagination of Mawlana as one of the Iraqi application style, in (Ghazalakani shamsi mawlana)’s Diwan.
Keywords: Mawlawi; Style; Types of styles Iraqi style; Linguistics; Literary